Answer:
C
Step-by-step explanation:
the answer is C
( -6 , 1 )
y = -1/2x - 2
if x = -6
y = -1/2(-6) - 2
y = 3 - 2
y = 1
The answer to the question is 0
Answer:the length of each side of the larger square is 6 centimeters.
Step-by-step explanation:
Let x represent the length of each side of the small square.
Let y represent the length of each side of the Large square.
The area of the small square is x^2
The area of the large square is y^2
The combined area of two squares is 45 square centimeters. This means that
x^2 + y^2 = 45 - - - - - - - - - - -1
Each side of one square is twice as long as a side of the other square. This means that
y = 2x
Substituting y = 2x into equation 1, it becomes
x^2 + (2x)^2 = 45
x^2 + 4x^2 = 45
5x^2 = 45
x^2 = 45/5 = 9
x = √9 = 3
Substituting x = 3 into y = 2x, it becomes
y = 2 × 3 = 6 centimeters